A festa do carro de boi no processo formativo audiovisual com os alunos do ensino fundamental II, em Cícero Dantas-BA - Ribeiro, Nilton Alex Fernandes (2021)
The Ox Cart Festival is one of the most traditional festivals in the city of Cícero Dantas - BA, this manifestation of popular culture transforms labor into parties for people who work hard in the suffering life of the countryside. From a study based on a quantitative perspective, using school subjects, as the main element of the audiovisual formative process through the ox cart party. This dissertation aimed to understand the insertion of audiovisual production, as a pedagogical resource for the study of popular culture: the Festa do Carro de Boi in Cícero Dantas - BA. The active methodology of the possibility to invest in popular culture at school based on technologies with collaborative audiovisual production with students. The study is justified based on its importance for the field of study of Popular Cultures and for the valorization of the cultural manifestations present in the municipality, mainly for the festivity of the ox cart, as it is part of the students' daily life, since many of them have in their families someone who participates in the party, or who owns the ox cart, or even makes them. This manifestation is part of the daily life of many who live in the surrounding cities. Aiming to understand topics that bring up the concern about the use of technological resources as tools that help the teaching-learning process. Training through the audiovisual formative process aims to strengthen cultural practices in the school environment and strengthen the manifestations of popular cultures.